2018
DOI: 10.1002/ejhf.1119
|View full text |Cite
|
Sign up to set email alerts
|

Transcoronary concentration gradients of circulating microRNAs in heart failure

Abstract: The present findings suggest that circulating levels of miRNAs are differentially expressed in patients with HF of different aetiologies. The presence of a transcoronary concentration gradient suggests a selective release of miRNAs by the failing heart into the coronary circulation. The presence of aetiology-specific transcoronary concentration gradients in HF patients might provide important information to better understand their role in HF, and suggests they could be useful biomarkers to distinguish HF of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 35 publications
1
68
0
1
Order By: Relevance
“…Correspondingly, the involvement of novel biomarkers in inflammatory processes was also observed in our study, reflected by a significant correlation of all markers with CRP. In addition to novel biomarkers tested in our project, latest studies also proposed an analysis of micro-RNA expression patterns as a novel diagnostic approach in heart failure [32][33][34]. On this regard, De Rosa et al could show, that transcoronary concentration gradients of circulating microRNAs could help to distinguish between different heart failure entities [33].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Correspondingly, the involvement of novel biomarkers in inflammatory processes was also observed in our study, reflected by a significant correlation of all markers with CRP. In addition to novel biomarkers tested in our project, latest studies also proposed an analysis of micro-RNA expression patterns as a novel diagnostic approach in heart failure [32][33][34]. On this regard, De Rosa et al could show, that transcoronary concentration gradients of circulating microRNAs could help to distinguish between different heart failure entities [33].…”
Section: Discussionmentioning
confidence: 89%
“…In addition to novel biomarkers tested in our project, latest studies also proposed an analysis of micro-RNA expression patterns as a novel diagnostic approach in heart failure [32][33][34]. On this regard, De Rosa et al could show, that transcoronary concentration gradients of circulating microRNAs could help to distinguish between different heart failure entities [33]. Similar to biomarkers in our study, circulating and exosomal micro-RNAs were also shown to correlate with clinical parameters such as left ventricular function in former studies [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…In combination with other researchers 'statistics on sample size, we selected more than 60 healthy samples and more than 60 cases of heart failure. Exhaustion samples were analyzed [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As shown in Figure 1, the aim of the present study was to identify circulating miRNAs in human plasma as biomarkers for the diagnosis of heart failure and its related diseases, to assess the appropriate biomarkers for identifying key characteristics of miRNAs, and to analyze their performance.…”
Section: Introductionmentioning
confidence: 99%
“…A number of circulating microRNAs are known to be altered in cachexia and sarcopenia [20,21]. Interestingly, among screened microRNAs, several are also candidate markers in heart failure [22,23], as well as some cachexia-related circulating microRNAs, such as microRNA-21 and microRNA-133, and are promising biomarkers in heart failure thatmight be able to help distinguish underlying etiology, including cachexia [24].…”
Section: Discussionmentioning
confidence: 99%